Molecular phylogeny of the megadiverse insect infraorder Bibionomorpha sensu lato (Diptera) - Ševčík, Jan; Kaspřák, David; Mantič, Michal; Fitzgerald, Scott; Ševčíková, Tereza; Tóthová, Andrea; Jaschhof, Mathias (PeerJ, 2016)
The phylogeny of the insect infraorder Bibionomorpha (Diptera) is reconstructed based on the combined analysis of three nuclear (18S, 28S, CAD) and three mitochondrial (12S, 16S, COI) gene markers. All the analyses strongly support the monophyly of Bibionomorpha in both the narrow (sensu stricto) and the broader (sensu lato) concepts. The major lineages of Bibionomorpha sensu lato (Sciaroidea, Bibionoidea, Anisopodoidea, and Scatopsoidea) and most of the included families are supported as monophyletic groups. Axymyiidae was not found to be part of Bibionomorpha nor was it found to be its sister group. Bibionidae was paraphyletic with respect to Hesperinidae and Keroplatidae was paraphyletic with respect to Lygistorrhinidae. The included Sciaroidea incertae sedis (except Ohakunea Edwards) were found to belong to one clade, but the relationships within this group and its position within Sciaroidea require further study.
Keywords: Lower Diptera; Molecular markers; Phylogenetic analysis; Systematics; Sciaroidea